2001
DOI: 10.1063/1.1402639
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of illumination on ferroelectric properties of lead zirconate titanate thin films

Abstract: Photosensitive ferroelectric materials exhibit various photoferroelectric phenomena due to the strong influence of nonequilibrium charge carriers on polarization and phase transition. These phenomena are essential for a number of applications including photodriven actuators and sensitive photodetectors. In this work, the effect of UV illumination on dielectric and piezoelectric properties is investigated in lead zirconate titanate (PZT) thin films, which are currently the most promising material for microactua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 14 publications
1
31
1
Order By: Relevance
“…4,5,9 In those experiments, poling of a capacitor into the negative polarization state with simultaneous UV illumination led to a positive shift of the hysteresis loop, while in our experiments the loops of the negative grains are shifted to negative voltages under UV light. The same situation ͑with opposite sign͒ held for the positive polarization state.…”
Section: B Screening Effects and Photoinduced Hysteresis Changesmentioning
confidence: 84%
“…4,5,9 In those experiments, poling of a capacitor into the negative polarization state with simultaneous UV illumination led to a positive shift of the hysteresis loop, while in our experiments the loops of the negative grains are shifted to negative voltages under UV light. The same situation ͑with opposite sign͒ held for the positive polarization state.…”
Section: B Screening Effects and Photoinduced Hysteresis Changesmentioning
confidence: 84%
“…It was found that UV light illumination helps the polarization restoration after severe fatigue in polycrystalline PZT films. [21][22][23] This was explained by generation of additional mobile carriers which might play a significant role in a rapid compensation of the polarization charges and by the "erasing" of the charge defects that can act as pinning centers for the ferroelectric domains.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous report, the magnetic field and pressure can slightly change the ferroelectric hysteresis loop, and the relative change of the saturated ferroelectric polarization was less than 20% at room temperature [28,33]. In addition, the minor light-induced change of ferroelectric polarization has already been observed in some ferroelectric compounds [34][35][36][37], however, it has never been reported in (anti/ferro/ferri) magnetic compounds and magnetoelectric ones. In a previous report, the light-induced change of ferroelectric polarization in ferroelectric compounds was explained by trapping of photogenerated charge at domain boundaries to minimize internal depolarizing fields [35][36][37].…”
mentioning
confidence: 76%
“…In addition, the minor light-induced change of ferroelectric polarization has already been observed in some ferroelectric compounds [34][35][36][37], however, it has never been reported in (anti/ferro/ferri) magnetic compounds and magnetoelectric ones. In a previous report, the light-induced change of ferroelectric polarization in ferroelectric compounds was explained by trapping of photogenerated charge at domain boundaries to minimize internal depolarizing fields [35][36][37]. The observed remarkable improvement in the ferroelectric polarization of the single-crystalline BiFeO 3 nanoribbons should be attributed to the photogenerated charge (see Supplementary Information for ferroelectric measurement details).…”
mentioning
confidence: 93%